Boston Scientific and Medinol : a bad alliance leads a company to do stupid things - Nagy, Andrea (SAGE knowledge. Cases., 2016)
Boston Scientific and Medinol sought a mutually beneficial alliance, signing a ten-year agreement that Boston Scientific would distribute and market Medinol's stents. But the alliance quickly deteriorated and, before the parties would finally reach a court settlement in 2005, there would be layoffs and recalls, suits and countersuits, threats to cut off manufacturing and the construction of a secret factory in Ireland. This case explains how a business relationship, created with the best of intentions, could go badly awry.